Zilpaterol-HCl reduces urinary excretion of N-tau-methylhistidine by finishing steers - D.W. Brake; Evan C. Titgemeyer (Kansas Agricultural Experiment Station Research Reports, 2011)
Zilpaterol-HCl is an orally active b-adrenergic agonist that repartitions nutrient use in cattle and has been approved for use during the final 20 to 40 days of the finishing period. Zilpaterol administration to finishing cattle increases average daily gain, feed efficiency, hot carcass weight, ribeye area, and dressing percentage; however, zilpaterol decreases meat tenderness, which is detectable by sensory panelists. Attenuation of zilpaterol's effect on tenderness would improve its benefits to cattle producers. Decreases in tenderness of meat from cattle fed zilpaterol may be closely related to decreases in protein degradation in skeletal muscles. Urinary excretion of N-tau-methylhistidine (NMH) in cattle reflects skeletal muscle protein degradation in vivo and provides a convenient research measure of muscle protein degradation. We analyzed NMH excretion by cattle fed zilpaterol to estimate the breakdown rate of skeletalmuscle protein.
Keywords: Kansas Agricultural Experiment Station contribution; no. 11-171-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 1047; Cattlemen& #x27; s Day; 2011; Beef; Zilpaterol-HCl; Finishing steers; Protein